Sonolithography: Sonolithography: In‐Air Ultrasonic Particulate and Droplet Manipulation for Multiscale Surface Patterning (Adv. Mater. Technol. 3/2021). Issue 3 (8th March 2021) - Shapiro, Jenna M.; Drinkwater, Bruce W.; Perriman, Adam W.; Fraser, Mike
Abstract : In article number 2000689, Jenna M. Shapiro, Mike Fraser, and co‐workers introduce sonolithography, a flexible and accessible fabrication technique harnessing in‐air ultrasonic standing waves. Particles and droplets are gently manipulated as they migrate through the acoustic pressure field, generating reliably and repeatably patterned surfaces. Sonolithography is applicable to a wide range of both deposited and substrate materials, and is shown to have potential in biofabrication with creation of a patterned cell culture substrate. (Image credit: Matt Sutton).